Contemporary globalization and teritorrialisation of society - Petrović, Mina (Teorija in praksa, 2014)
Paper starts with the link between contemporary globalisation and processes of de-territorialisation and re-territorialisation of society, which helps understanding the separation of social from state territoriality and increasing importance of other territorial scales (both sub national and supranational) in a numerous social issues. The paper aims to analyse identity dimension of these processes in two aspects. Firstly, it focuses on changing territorial identity of individuals regarding the weakening of their attachment to the nation-state and strengthening of their attachment to other territorial scales, primarily to the immediate local environment and then to supranational one (as EU). Secondly, re-territorialisation of citizens' identity (increasing attachment to place of living in an open and relational manner) is analysed as potentially valuable local developmental resource within globalising societies, as emphasized in EU territorial agenda. Both issues are important for Serbia, as well as for other European post-socialist societies, whose globalisation and recent de-re-territorialisation take place under the significant influence of EU. The analysis relies on empirical data obtained through questionnaire research conducted on a representative sample (N=2557) of citizens in Serbia by Institute for Sociological Research at the Faculty of Philosophy University of Belgrade, in spring 2012. The research findings show that territorial identity of citizens in Serbia develops in accordance to the principles of selective associations and multiple loyalties, but that new localism and glocalism as desirable development resources still have not been sufficiently profiled.
Keywords: Globalizacija; Globalization; Localism; Lokalizem; Prostorska sociologija; Serbia; Spatial sociology; Srbija; teritorialna identiteta